2005
DOI: 10.1016/j.febslet.2005.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane and lysosomal localization of CB1 cannabinoid receptor are dependent on lipid rafts and regulated by anandamide in human breast cancer cells

Abstract: In this report we show, by confocal analysis of indirect immunofluorescence, that the type-1 cannabinoid receptor (CB1R), which belongs to the family of G-protein-coupled receptors, is expressed on the plasma membrane in human breast cancer MDA-MB-231 cells. However, a substantial proportion of the receptor is present in lysosomes. We found that CB1R is associated with cholesterol-and sphyngolipid-enriched membrane domains (rafts). Cholesterol depletion by methyl-b-cyclodextrin (MCD) treatment strongly reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
71
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 46 publications
6
71
1
Order By: Relevance
“…In human breast cancer cells, CB1 is physically associated with lipid rafts in a cholesterol-dependent manner, and this association can be dynamically modified by AEA binding (775). This spatial and functional coupling between CB1 and lipid rafts was also shown in an ex vivo model of striatal neurons, where raft disruption by cholesterol depletion causes a marked increase of CB1 binding and activity (503).…”
mentioning
confidence: 74%
“…In human breast cancer cells, CB1 is physically associated with lipid rafts in a cholesterol-dependent manner, and this association can be dynamically modified by AEA binding (775). This spatial and functional coupling between CB1 and lipid rafts was also shown in an ex vivo model of striatal neurons, where raft disruption by cholesterol depletion causes a marked increase of CB1 binding and activity (503).…”
mentioning
confidence: 74%
“…Furthermore, direct agonists of CB 1 and CB 2 receptors, i.e., arachidonoylchloroethanolamide and JWH-133, were also less potent and efficacious than cannabidiol at inhibiting MDA-MB-231 cell growth (data not shown). We also studied in MDA-MB-231 cells the effect of cannabidiol (5 M) after a 10-min exposure to methyl-␤-cyclodextrin (0.5 mM), a potent membrane cholesterol depleter that is able to destroy the lipid raft microdomains and to block the clustering of CB 1 at the plasma membrane in MDA-MB-231 cells (Sarnataro et al, 2005). We found no significant effect on the inhibitory action of cannabidiol (from 29.9 Ϯ 3.5% to 30.2 Ϯ 3.6% inhibition, mean Ϯ S.E.…”
Section: Cannabidiol In Cancer 1381mentioning
confidence: 99%
“…Interestingly, we have previously found that CB1R is associated with lipid rafts/caveolae in MDA-MB-231 breast cancer cells (Sarnataro et al, 2005). Furthermore, CB1 plasma membrane distribution and its raft association are dependent on cholesterol levels and on ligand binding, suggesting that the membrane distribution of the receptor is dependent on rafts and is possibly regulated by the agonist binding.…”
mentioning
confidence: 99%